In-situ observation of twinning and grain rotation assisted deformation in wire-arc direct energy deposited (WDED) single phase titanium - Blanca Palacios; Sohail M.A.K. Mohammed; Tanaji Paul; Brandon Aguiar; Sean Langan; Arvind Agarwal (Journal of Materials Research and Technology)
Additive manufacturing of metals often results in microstructural inhomogeneities, leading to the simultaneous or sequential activation of multiple deformation mechanisms. Real-time monitoring of these mechanisms is essential for understanding material behavior. While Digital Image Correlation (DIC) effectively evaluates strains during in-situ deformation, its accuracy diminishes at high strain levels, necessitating complementary techniques. This study integrates crystal orientation measurements from Electron Backscatter Diffraction (EBSD) with in-situ DIC to investigate deformation characteristics of wire arc directed energy deposited (WDED) single α-phase titanium. Quasi-in-situ tensile tests were conducted to model and validate twin traces focusing on twin system activation guided by crystal orientation and Schmid factor (m) calculations. The (011‾2) [01‾11] twin system displayed the maximum Schmid factor (m = 0.383), indicating a strong propensity for twinning, while the twin system (1‾102) [11‾01] exhibited the least m of 0.0015, exhibiting minimal twin activity during tensile deformation. The twin traces were validated using Schmid factor calculations, which reflect the tendency of preferential deformation twinning in WDED titanium. These findings reveal preferential deformation twinning behavior in WDED titanium, providing insights into the underlying deformation mechanisms and offering directions for the advancement of additively manufactured high-strength structural materials.